Toxicity of the yellow puffer fish Xenopterus naritus from Sungai Saribas, Sarawak - Othman, Bojo; Khairul Adha, A. Rahim; Samsur, Mohamad; M.L., Shabdin; Nyanti, Lee; Norhadi, Ismail; Po Teen, Lim (-, 2014)
Despite common fish poisoning, puffer fish is still considered as a delicacy in Japan and China. Most of the poisoning cases occur after consuming marine puffer fish species. The principle toxin exists in puffer fish is known as tetradotoxin (TTX). In freshwater puffer fish species, paralytic shellfish toxins (PSTs) have also been detected besides the TTX. Studies have shown that the highest toxin content was found in the skin, followed by gonad, muscle, liver and intestine.